An Analysis of Code Switching Used in The Architecture of Love Novel Written by Ika Natass - Ni Ketut Febriyanti (Humanitatis : Journal of Language and Literature, 2019)
NI KETUT FEBRIYANTI. An Analysis of Code Switching used in ‘The Architecture of Love’ novel written by Ika Natassa. S1 Thesis. Mataram: Bumigora University, 2019This research aims to analyze Code-Switching in The Architecture of Love novel written by Ika Natassa. The researcher obtained the data from chapter to chapter in the novel that consists of 22 chapters. This research used the descriptive qualitative method, technique of data analysis uses 1) Reading the novel, 2) Transcribing the code-switching utterances, 3) classifying which of the data consists of code switching’s type and function, 4) Drawing the conclusion. The finding showed that there were 203 data of code-switching in the novel that consist of three types of code-switching. The highest frequent was Intra-sentential switching with 90 data found, the second one is Inter-sentential switching with 83 data and the lowest is Tag-sentential switching with 30 data, and about the function of code-switching, the highest frequent was Message Qualification with 9 data and also Interjection with 8 data. The Addressee Specification has 4 data, Quotation has 2 data and the lowest frequent are Reiteration and Personalization vs. Objectivization with 1 datum.